2003
DOI: 10.1038/sj.mp.4001462
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl-eicosapentaenoic acid ingestion prevents corticosterone-mediated memory impairment induced by central administration of interleukin-1β in rats

Abstract: Central or peripheral administration of the proinflammatory cytokine interleukin (IL)-1b can impair performance on spatial memory tasks and also elevate circulating concentration of corticosterone. The present experiment provides independent confirmation that intracerebroventricular administration of 10 ng IL-1b in the rat can have a selective effect on the retrieval of trial unique information about the location of food on an eight-arm radial maze. The probable involvement of corticosterone in IL-1b-induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 53 publications
5
47
0
1
Order By: Relevance
“…For instance, a systemic or intraventricular IL-1β injection gives rise to spatial memory impairments in rats, 59,60 and significant effects of injected IL-1β on the win-shift paradigm of the radial arm maze have been reported. 61 Bickford et al have previously shown that an indirect IL-1 blockade, using a caspase ***-1 inhibitor, has significant improvement effects on memory in aged rats, suggesting that IL-1 is involved in impaired performance on memory tasks with aging. 62 IL-1 has also been shown to be an important player in inflammation-induced memory impairments in rodents, following a chronic inflammation paradigm.…”
Section: High-fat Diets and Cognitionmentioning
confidence: 99%
“…For instance, a systemic or intraventricular IL-1β injection gives rise to spatial memory impairments in rats, 59,60 and significant effects of injected IL-1β on the win-shift paradigm of the radial arm maze have been reported. 61 Bickford et al have previously shown that an indirect IL-1 blockade, using a caspase ***-1 inhibitor, has significant improvement effects on memory in aged rats, suggesting that IL-1 is involved in impaired performance on memory tasks with aging. 62 IL-1 has also been shown to be an important player in inflammation-induced memory impairments in rodents, following a chronic inflammation paradigm.…”
Section: High-fat Diets and Cognitionmentioning
confidence: 99%
“…Chronic low-grade systemic inflammation plays a significant role in several chronic medical diseases as well as depression [78] . Interestingly, animals fed high AA diet or treated with PGE2 produced sickness behaviours of anorexia, low activity, change in sleep pattern and attention [56,57] . n-3 PUFAs have an anti-inflammatory effect by antagonizing membrane AA and reducing PGE2 synthesis [79] .…”
Section: Biological Mechanism Of the Effect Of N-3 Pufas On Depressiomentioning
confidence: 99%
“…An AA-enriched diet can increase glucocorticoid and PGE2 secretion as well as anxiety behaviour [54] . In contrast, EPA can suppress proinflammatory effects of AA [55] , thereby reducing PGE2 synthesis [55] and attenuating interleukin (IL)-1 ␤ -induced activation of PGE2 [56] . Foods enriched with ethyl-EPA, but not soybean oil, significantly attenuated most of the IL-1 ␤ -induced sickness, stress and anxiety-like behaviours [57] .…”
Section: Role Of N-3 Pufas In Sickness Behaviour and Somatic Symptomsmentioning
confidence: 99%
“…Furthermore, expression of IL-10 is also blocked by ethyl-EPA treatment. Based on these results, it is proposed that ethyl-EPA treatment produces beneficial effects in those neuropsychiatric disorders in which inflammation and oxidative stress play a critical role (Song et al, 2004;Song et al, 2009;Farooqui, 2009).…”
Section: Dha In the Brainmentioning
confidence: 94%
“…Thus, inadequacy of EPA and DHA in neural membranes may contribute to cholinergic, dopaminergic, and glutamatergic receptor dysfunction in synapses associated with the hippocampal neurons, and growing evidence suggests that low levels of DHA in the brain are associated not only with neurotraumatic, neurodegenerative, and neuropsychiatric diseases, but also with peroxisomal disorders (Farooqui, 2009). Dietary intake of EPA antagonizes the synthesis of PGE 2 from ARA and reduces the IL-1β-mediated increase in levels of PGE 2 (Song et al, 2004;Song et al, 2009). Furthermore, expression of IL-10 is also blocked by ethyl-EPA treatment.…”
Section: Dha In the Brainmentioning
confidence: 98%